The Impact of Work Familiy Conflict on the Performance of Women Employees: a Scope Review - Mufidah, Imroatul; Ratnawati, Ratnawati; Rahayu, Yayuk Ngesti (Formosa Journal of Applied Sciences, 2024)
This study of the research aims to shed light on how work-family conflict affects employee performance, particularly for female employees. The purpose of a scoping review is to find relevant literature that has been thoroughly and in-depthly gathered from various sources using a range of research techniques. The majority of the literature review's findings point to the influence of work-family conflict on employee performance. Roboth (2015) and Prianggi et al. (2022) on the other hand, presented contrasting findings and concluded that work-family conflict did not influence output.